Preoperative Anaemia Increases the Likelihood of 1-Year Mortality After Hip Fracture - Helena Ferris; Gavin Sedgwick; Mitchell Marnane; Sean Clarke; Ann Dwyer; Georgia Merron; Tara Coughlan (Advances in Orthopedics)
Conclusion: Anaemia is common in hip fracture patients and may be viewed as a surrogate marker of frailty. In this cohort, Hb ≤ 10 g/dL on admission was a statistically significant predictor of 1-year mortality. Recognising and managing anaemic patients preoperatively may provide an opportunity to improve longer-term outcomes in hip fracture patients.